Antigens of gastric and intestinal mucous cells in human colonic tumours. - Bara, J. (Nature Publishing Group, 1980)
Using immunofluorescence methods, 3 antisera respectively stain 3 groups of mucous cells of the human gastrointestinal tract, showing specific antigens for each group of cells. The antigens of the first group, the M1 antigens, were principally associated with columnar cells of the gastric epithelium, the M2 antigens with mucous cells of gastric and Brünner's glands, and the M3 antigen with the goblet cells of the intestinal mucosa. The gastric M antigens normally detectable in stomach and duodenum (but not in colon) were expressed in certain colonic tumours (benign or malignant) and in adjacent mucosa. They are always present with the intestinal M3 antigen. In 100 colonic adenocarcinomas, the intestinal M3 antigen was found in 53 cases, gastric M1 antigens in 29 cases, and gastric M2 antigens in 10 cases, always with the two other M antigens. A good correlation could be established between the association of M antigens and the histological type of tumour. IMAGES: